Conceptualisation of Nation within Polish Modern Public Discourse - Żywicka, Beata (Vilnius University Open Series, 2020)
While attempting to reconstruct the Polish understanding of the word “nation”, the author applies three different data types, however complementary to one another (i.e. systemic, questionnaire and text data). By referring to the word etymology and dictionary definitions, the author portrays a multifaceted model of nation as the community of people (the psychosocial aspect) who live within a particular territory, speak one common language, have common cultural background (the cultural aspect), similar world view (the ideological aspect), pursue common economic (the living-standard aspect) and political interests.The analysis of the quoted texts, the questionnaires collected among the students in the years 1990, 2000 and 2010 shows certain significant differences that mainly concern the political and ideological spheres. It is noticeable that in 1990 the desire for independence was stronger among the young people than it was among their peers twenty years later and was connected with the political transformation that Poland underwent in 1989 when after years spent behind the “Iron Curtain” the nation could finally openly realise the ideals of freedom and enjoy life in the state that is independent, autonomous and democratic.The Polish contemporary journalistic texts accompanied by the scientific considerations and discussions present the nation in three categories: the political, territorial and cultural, biological. The nation seen from the political perspective is a collective of individuals having political rights, common laws and bound with one another by mutual duties, and by residing on a particular geographical territory they can form a state. In the press articles as well as certain Catholic church representatives’ statements, there appears a cultural concept of the nation seen as the community formed by the individuals and groups that are bound by common culture (language, traditions, customs), history, religion and pursued values. The biological concept of the nation refers to the principle of consanguinity. It relies on the assumption that strong blood ties constitute the basis for nation’s existence and one of the significant components of national consciousness.
Keywords: nation; value; aspect; cognitive definition